Establishing a workflow for gastroenteritis virus surveillance, and norovirus whole genome characterisation by next-generation sequencing technologies - Mans, Janet (University of Pretoria, 2024)
Dissertation (MSc(Medical Virology))--University of Pretoria, 2024.